Evaluation of Early Growth Traits and Herbage Biomass Production of Selected Oat Genotypes Under Different Sowing Dates - Regmi, Saroj; Devkota, Naba Raj; Ghimire, Ram Prasad; Barsila, Shanker Raj (Journal of Agriculture and Forestry University, 2026)
Early growth traits are important indicators of plant vigor and potential herbage yield. Lack of knowledge on how early growth traits respond to different sowing dates and their influence on herbage biomass is limiting oat fodder production in the Terai region. Optimum sowing date can enhance livestock feed availability and quality through higher herbage biomass production. The objective of this study was to evaluate early-stage growth attributes and herbage yield under different sowing dates. A field experiment was conducted using a two-factor factorial randomized complete block design with four replications at Rampur, Chitwan. Four oat genotypes (Nandini, Amritdhara, Swan Pak, and Longford) were sown on three dates: 1 November, 15 November, and 30 November. Significant differences (p